Hybrid Gold/Silica/Quantum-Dots supramolecular-nanostructures encapsulated in polymeric micelles as potential theranostic tool for targeted cancer therapy. (August 2018) - Li Volsi, Anna; Fiorica, Calogero; D'Amico, Michele; Scialabba, Cinzia; Palumbo, Fabio Salvatore; Giammona, Gaetano; Licciardi, Mariano
Graphical abstract: Highlights: Polymeric micelles containing both Doxorubicin and gold core-shell quantum dots. Nanosystems with antitumor and photothermal effect. Theranostic nanoplatform with multiple therapeutic effect. Abstract: Efficient theranostic tools are today more and more frequently represented by the nano-sized systems. In this paper, polymeric micelles were produced and exploited to encapsulate both an antitumor drug (Doxorubicin) and gold core–shell quantum dots nanoparticles (Au-SiO2 /QDs). α, β-poly(N-hydroxyethyl)-dl -aspartamide (PHEA) was functionalized with lipoic acid (LA), polyethylenglycol (PEG), and folic acid (FA) pendant moieties to obtain a synthetic derivative (PHEA-LA-PEG-FA) able to self assemble in aqueous medium giving rise to the formation of polymeric micelles exposing on their surface both targeting groups (FA) and hydrophilic chains (PEG). The drug carrying ability of PHEA-LA-PEG-FA micelles was here studied along with the cytotoxity of the obtained nanostructures toward breast cancer cells employing doxorubicin as a model anticancer drug. Finally, the properties of the gold-shell QDs incorporated into the micelles as cells imaging agent and photothermal anticancer treatment tool were explored.